EFEKTIVITAS PELAYANAN ADMINISTRASI ELEKTRONIK KARTU TANDA PENDUDUK (KTP-el) DI UPTD KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Simorangkir, Desi Fitriani; Tua, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Districs North Tambusai is one of the Northern Tambusai Sub-district is one of the districts in the Rokan Hulu Regency. North Tambusai Sub-district is also one of the areas that is implemented the program of KTP-el. Based on the results of research that is still found many residents of communities who have note done recording KTP-el. The data of residence of Sub-district of Tambusai North 2016 shows the total population about 56.871 people. While those who haven’t done the recording amouted to 13.211 people. Still many people who haven’t done recording, showed the lack of effectiveness of services pravided to public and also many still of information about KTP-el. The purpose of thisstudy is determine the effectiveness of the implementation of data Departement of Population and Civil Registration Northern Tambusai and to know the factors that influence the effectiveness of KTP-el service. The study uses a qualitative method. The data source is taken from the primary and secondary data. In data collection, researchers used interview techniques, observation and documentation. The informant is the head of Disdukcapil North Tambusai, Northern Tambusai Camat, Staff Employees Disdukcapil and Community while the data analysis techniques used is descriptive qualitative analysis. The result of the study show that the effectiveness of administrative KTP-el service in the Northern Tambusai District in terms of data recording is still achieved although there are still some indicators that have not been maximized in implementation. And from the target data recording expected by Disdukcapil Sub-district of Northem Tambusai only reach 70%. As well as factors affect the effectiveness of KTP-el services in the Departement of Population and Civil Registration Northern Tambusai is Employee Discipline, Public awareness about KTP-el and internet-conection which is often disconnected.Keywords: KTP-el, Effectiveness, Service